Early-stage assessment of a flexible aircraft simulation framework in a pilot-in-the-loop environment - Bragado Aldana, Estela; Whidborne, James F.; Alam, Mushfiqul (American Institute of Aeronautics and Astronautics (AIAA), 2025)
Accurate prediction of the interactions between aeroelastic effects, flight control, and flight dynamics is essential for evaluating the handling qualities and safety of future aircraft concepts. This paper reports on the development of an advanced modelling and simulation framework for assessing the impact of airframe flexibility on flight dynamics within a real-time pilot-in-the-loop environment. As part of this, a series of shakedown trials were conducted using a model of a Saab 340B to test system integration, pilot interaction, and dynamic response through open-loop manoeuvres. These tests were supported by subjective fidelity ratings using the Simulation Fidelity Rating (SFR) scale to evaluate the framework’s readiness for formal handling qualities assessments. Pilot feedback confirmed the general suitability for such evaluations, while also identifying perceptual and modelling limitations. This research demonstrates the feasibility and value of integrating multidisciplinary modelling tools with piloted simulation and establishes a foundation for the forthcoming handling qualities evaluation campaign.